2021
DOI: 10.3390/biology10060483
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesviruses Increase the Severity of Hepatitis

Abstract: Acute and chronic liver diseases are a major global public health problem; nevertheless, the etiology of 12–30% of cases remains obscure. The purpose of this research was to study the incidence of human herpesviruses (HHVs) cytomegalovirus, Epstein–Barr virus (EBV), and HHV-6 in patients with hepatitis and to examine the effect of HHV on the disease severity. We studied the clinical materials of 259 patients with hepatitis treated in Infectious Clinic n.1 (Moscow) and the archived materials of 118 patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“… 127 128 Above findings were consistent with previous research. In fecal samples, most detected Herpesviridae such as herpesvirus‐6 128, 129 and herpesvirus‐8 130 , 131 are associated with the severity of ALD, and they could be classified into Epstein-Barr virus (EBV). EBV infection often causes liver inflammation, but the pathogenesis remains unknown.…”
Section: Gut Viromementioning
confidence: 99%
See 1 more Smart Citation
“… 127 128 Above findings were consistent with previous research. In fecal samples, most detected Herpesviridae such as herpesvirus‐6 128, 129 and herpesvirus‐8 130 , 131 are associated with the severity of ALD, and they could be classified into Epstein-Barr virus (EBV). EBV infection often causes liver inflammation, but the pathogenesis remains unknown.…”
Section: Gut Viromementioning
confidence: 99%
“…EBV infection often causes liver inflammation, but the pathogenesis remains unknown. 129 A retrospective study of patients with liver cirrhosis found that EBV-positive patients had higher Child-Pugh scores, more severe liver injury and a higher rate of chronic acute liver failure, 132 which suggested the reactivation of EBV might contribute to the development of alcoholic hepatitis.…”
Section: Gut Viromementioning
confidence: 99%
“…Production of memory B-cells is the first outcome, the second leads to differentiation of B-cells into plasma cells that are programmed [6] . EBV plays a role in liver inflammation by impacting hepatocytes directly or indirectly through immune cells [7]. EBV is linked to a variety of cancers and is the first human tumour virus to be found.…”
Section: Introductionmentioning
confidence: 99%
“…Epstein-Barr virus, and human herpesviruses (HHV) type 6 in biological samples of patients with liver cirrhosis as compared to those without advanced liver disease; furthermore, patients with herpesvirus coinfection showed a trend toward high rates of liver decompensation, hepatorenal syndrome, and portal hypertension [16]. Finally, Priora and colleagues recapitulated the rheumatologic manifestations of CHC (up to 38% of patients), and the differential diagnosis between the former and primary rheumatic diseases that may coexist in these patients [17].…”
mentioning
confidence: 99%
“…Yurlov and colleagues focused their attention on non-hepatotropic viruses as a cause or contributing cause in the occurrence, progression, and outcome of inflammatory liver diseases [ 16 ]. Specifically, the authors observed a high prevalence of cytomegalovirus, Epstein–Barr virus, and human herpesviruses (HHV) type 6 in biological samples of patients with liver cirrhosis as compared to those without advanced liver disease; furthermore, patients with herpesvirus coinfection showed a trend toward high rates of liver decompensation, hepatorenal syndrome, and portal hypertension [ 16 ]. Finally, Priora and colleagues recapitulated the rheumatologic manifestations of CHC (up to 38% of patients), and the differential diagnosis between the former and primary rheumatic diseases that may coexist in these patients [ 17 ].…”
mentioning
confidence: 99%